Considering The Patentability of Computer Software in Thailand: A Comparative Study with the United States, European Union, Japan and South Korea for AI Technology Development - Pornpattta, Panida (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2025)
The patentability of software or computer programs is an ongoing issue within legal and technical communities worldwide, especially with the rise of artificial intelligence (AI) and machine learning (ML) technologies. AI, which has rapidly become a leading area in global patent filings, impacts various fields, including speech recognition and natural language processing. The shift from physical to digital distribution has reshaped software use, making software patents an evolving area of law, with eligibility becoming more consistent across jurisdictions. This paper examines software patentability in Thailand by analyzing its legal framework and comparing it with practices in the United States, European Union, Japan and South Korea. In Thailand, computer programs are protected as literary works under the Copyright Act B.E. 2537 (1994), where they are defined as “instructions, sets of instructions, or other components used in conjunction with a computer to produce results.” In contrast, the Patents Act B.E. 2522 (1979) lacks a clear definition, referring only to “information systems for computer operation” in Section 9(3), leading to inconsistent interpretations and applications. The study addresses key questions, including how Thai laws might clarify the conditions under which software-related inventions are patentable, how the differences in legal definitions impact patent applications, and whether Thailand could benefit from adopting other countries’ practices. This paper suggests that Thailand should adopt clearer legal definitions distinguishing software-related inventions from literary works, as seen in other jurisdictions, and consider requiring technical contributions or inventive processes to promote innovation and better protect emerging technologies such as AI and ML.